2021
DOI: 10.1038/s41398-021-01560-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and cognitive function of magnetic seizure therapy vs. electroconvulsive therapy for major depressive disorder: a systematic review and meta-analysis

Abstract: Magnetic seizure therapy (MST) has established efficacy in the treatment of depression and a growing evidence base in the treatment of depression. We conducted the first systematic review and meta-analysis of the efficacy of MST in anti-depressive treatment and its impact on cognitive function (INPLASY registration number: INPLASY202170061). We searched for controlled trials published in English between 1 January 2001 to 31 December 2020 in PubMed, EMBASE, Cochrane Library, Web of Science, and PsycINFO databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Magnetic seizure therapy (MST) is a new physical therapeutic technique that uses alternating strong magnetic fields to perform generalized seizures for antidepressant-therapeutic purposes [ 12 , 13 , 14 ]. Numerous studies have proved that MST has similar antidepressant efficacy to ECT and few adverse effects in treating major depressive disorder (MDD) [ 15 , 16 , 17 , 18 , 19 ]. Similarly, a recent systematic review reported that MST, as an adjunctive treatment, was efficacious for total psychopathology in schizophrenia [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic seizure therapy (MST) is a new physical therapeutic technique that uses alternating strong magnetic fields to perform generalized seizures for antidepressant-therapeutic purposes [ 12 , 13 , 14 ]. Numerous studies have proved that MST has similar antidepressant efficacy to ECT and few adverse effects in treating major depressive disorder (MDD) [ 15 , 16 , 17 , 18 , 19 ]. Similarly, a recent systematic review reported that MST, as an adjunctive treatment, was efficacious for total psychopathology in schizophrenia [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Kayser et al reported that up to 69% of patients with TRD responded to MST ( 46 ). The latest meta-analysis (10 studies, 285 patients) found that MST produces a similar antidepressant effect to ECT ( 38 ). Furthermore, the optimal parameters of MST need to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence shows that MST is associated with relatively fewer neurocognitive adverse effects than ECT for major depressive disorder (MDD) ( 36 , 37 ). In a recent meta-analysis, MST was associated with shorter recovery and reorientation times and lower cognitive impairment for MDD than ECT ( 38 ). However, inconsistent findings have been reported in two studies on patients with schizophrenia receiving MST treatments ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, a recent pilot study comparing 100 Hz MST with ECT found no differences in antidepressant effectiveness between the two approaches 12 . Crucially, MST does not appear to be associated with the cognitive side effects observed after ECT 14 , which is a pertinent advantage for individuals with BPD who show a range of cognitive deficits, including in episodic memory 15 .…”
Section: Suicidal Ideationmentioning
confidence: 96%